Radial force control of Multi-Sector Permanent Magnet machines considering radial rotor displacement - Valente, G.; Papini, L.; Formentini, A.; Gerada, C.; Zanchetta, P. (2017)
A mathematical model enabling to predict the electromagnetic x-y forces and torque for a given input current in a Multi-Sector Permanent Magnet Synchronous (MSPMS) machine is presented. The rotor static eccentricity is also accounted and the analytical calculations are validated by means Finite Element Analysis (FEA). Furthermore, a novel force and torque control is proposed based on input current minimization and is applied to suppress the Unbalanced Magnetic Pull (UMP) caused by the rotor eccentricity. The effective operation of the force suppression technique is verified by means of FEA.